Post-disaster recovery in small towns: learning from the experience of tornado recovery in two communities - Walls, Natalie Kate (Kansas State University, 2024)
Tornadoes are a type of natural disaster that can occur anywhere in the world and cause massive amounts of destruction and loss of life. Since tornadoes develop rapidly and can occur anywhere, they are very difficult to predict, and communities have trouble properly preparing for and ultimately recovering from them. Tornadoes can be even more devastating for small rural communities that are already struggling to sustain their population base. The overarching goal of this study is to explore, what response and recovery strategies contribute to long-term recovery, including population recovery, in small communities? We applied a comparative case study approach for the cities of Greensburg, Kansas, and Parkersburg, Iowa, both of which experienced EF-5 tornadoes in 2007 and 2008 respectively but had different paths toward tornado recovery. While Parkersburg succeeded in recovering and growing its population post-tornado, Greensburg continued to lose population over time. Through key informant interviews and document analysis, the strategies they have implemented to recover are explored and the strategies that worked well and that didn’t in terms of long-term recovery are identified. Some strategies that have supported recovering communities like Parkersburg and Greensburg with varying levels of success include rebuilding the basic needs of the community first, having a pro-growth strategy that capitalizes on the build-back better mindset, and marketing the cities’ unique characteristics such as new infrastructure and supply of buildable lots. Having a hazard mitigation and disaster recovery plan in place and accelerating the planning process so the population doesn’t move elsewhere also helped these communities. These strategies show the importance of disaster preparedness and rapid planning initiatives post-disaster for the long-term recovery of small communities. Findings from this study can contribute to the planning initiatives of other small towns in tornado-prone areas in hopes of easing their recovery processes.
Keywords: Disaster recovery; Tornadoes; Disaster planning; Hazard mitigation